2013
DOI: 10.1111/joor.12088
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the thickness of silicone registration material as a means for occlusal contact examination – an explorative study with different tooth clenching intensities

Abstract: This study explored the influence of the thickness of silicone registration material on evaluation of the occlusal contact area and number of occlusal contact points, during increasing tooth clenching conditions in normal subjects. Twenty-four subjects with no more than one missing tooth per quadrant participated. Surface electro-myography was recorded from the masseter muscle. As a baseline measurement, intercuspal position was maintained with minimal force, and occlusal contact was recorded using blue silico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 44 publications
(54 reference statements)
1
17
1
3
Order By: Relevance
“…Silicone recording materials thicker than 5 mm were unable to calculate the OCA using this occlusal analysis device, therefore silicone recording materials were trimmed to less than 5 mm thick to maintain exact transmittance. As previously described (14), the OCA thicknesses were defined as level 1 (<150 µm: 0-149 µm), level 2 (<90 µm: 0-89 µm), level 3 (<50 µm: 0-49 µm), level 4 (<30 µm: 0-29 µm), and level 5 (<5 µm: 0-4 µm) in the image to calculate the OCA. The OCA in each tooth was divided using a maxillary tooth image on the computer screen and calculated from three jaw motor tasks according to the five thickness levels.…”
Section: Occlusal Contact Acquisition and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Silicone recording materials thicker than 5 mm were unable to calculate the OCA using this occlusal analysis device, therefore silicone recording materials were trimmed to less than 5 mm thick to maintain exact transmittance. As previously described (14), the OCA thicknesses were defined as level 1 (<150 µm: 0-149 µm), level 2 (<90 µm: 0-89 µm), level 3 (<50 µm: 0-49 µm), level 4 (<30 µm: 0-29 µm), and level 5 (<5 µm: 0-4 µm) in the image to calculate the OCA. The OCA in each tooth was divided using a maxillary tooth image on the computer screen and calculated from three jaw motor tasks according to the five thickness levels.…”
Section: Occlusal Contact Acquisition and Data Analysismentioning
confidence: 99%
“…Gurdsapsri et al compared OCAs at different levels of maximum voluntary tooth contraction (MVC) (10%, 30%, 70%, and 100%) controlled by electromyography (EMG) visual feedback, and observed a significant increase in the OCA with higher tooth clenching intensity (13). A previous study showed that occlusal contacts differed with low-intensity tooth clenching (14). However, the OCA has not yet been measured in individual teeth.…”
Section: Introductionmentioning
confidence: 99%
“…The silicone recording materials were trimmed to the appropriate thickness within 5 mm to keep the exact transmittance before the actual analysis. An occlusal analytic device (BITE EYE BE‐I, GC) was used for the analysis of the occlusal contact area and points . In the present study, occlusal contact area and point was defined as the thickness of silicone material was <30 μ m in silicone occlusal records, and the occlusal contact area and point were calculated for each task.…”
Section: Electromyography Analysismentioning
confidence: 99%
“…In the present study, occlusal contact area and point was defined as the thickness of silicone material was <30 μ m in silicone occlusal records, and the occlusal contact area and point were calculated for each task. The anterior zone and the left and right posterior zone were analysed separately following previous study . To evaluate repeatability between first and second occlusal contact area and point measurement, ICC was calculated from these values.…”
Section: Electromyography Analysismentioning
confidence: 99%
See 1 more Smart Citation